OS2.3 Updated results of REGOMA: A randomized, multicenter, controlled open-label phase II clinical trial evaluating regorafenib in relapsed glioblastoma <GBM> patients <PTS>. (19th September 2018) - Lombardi, G; de Salvo, G; Rudà, R; Franceschi, E; Eoli, M; Faedi, M; Pace, A; Lolli, I; Rizzato, S; Germano, D; Pasqualetti, F; Farina, M; et al.
Abstract: Background: There is no established treatment regimen for recurrent GBM. GBMs have activation of multiple signaling pathways in the tumor microenvironment, including the receptor tyrosine kinases, VEGFR, FGFR, and PDGFR. Regorafenib (REG), an oral multikinase inhibitor, inhibits these angiogenic kinases and the mutant oncogenic kinases KIT, RET, and B‐RAF. Material and Methods: We present, after the first analysis, the updated results of REGOMA trial. The primary aim of this trial was to assess REG activity in prolonging overall survival (OS) in PTS with relapsed GBM after surgery and Stupp regimen (α = 0.2, 1-sided; β = 0.2). Secondary objectives were PFS, disease control rate (DCR), safety, quality of life (QoL); exploratory objectives included analysis of metabolic tissue biomarkers as possible predictors of response. PTS with histologically confirmed GBM, ECOG PS 0‐1, documented disease progression were randomized 1:1 to receive REG 160 mg/day (3 weeks on, 1 week off) or lomustine (LOM) 110 mg/m2 (every 6 weeks) until disease progression or unacceptable toxicity. Tumor response was evaluated by brain MRI every 8 weeks according to the RANO criteria. Results: 119 PTS were randomized (n = 59 REG; n = 60 LOM) and stratified for surgery at recurrence; baseline characteristics, including MGMT methylation status, were balanced. Median age was 57.3 yrs; 27 PTS (22.7%) had surgery at recurrence, 22% and 23.3% in REG and LOM arm. At the time of analysis (cut-off date: Dec 31, 2017), median follow up was 15.4 months(m), 99 PTS had died. Median OS was 7.4m (95% CI 5.8–12.0) for REG and 5.6m (95% CI 4.7–7.3) for LOM (HR = 0.50, 80%CI 0.38–0.65; p = 0.0007; 1-sided Log-rank test); 12m-OS rates were 38.9% and 15.0% for REG and LOM. 6m-PFS rates were 16.9% and 8.3% (HR = 0.65; 95% CI 0.45‐0.95; p = 0.0223) for REG and LOM, DCR was 44.8% and 21.1% (p = 0.009) for REG and LOM. Grade ≥3 adverse events were reported in 56% and 40% for REG andLOM, no treatment-related deaths were reported. Conclusion: In this multicenter, randomized study, REG significantly improved OS, PFS and DCR in recurrent GBM PTS. REG treatment was feasible and well tolerated. QoL and biomarker analyses are ongoing. A phase 3 study will be planned